2018
DOI: 10.3390/md16110457
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Activity of Some Marine Fungal Metabolites in the 6-Hydroxydopamin- and Paraquat-Induced Parkinson’s Disease Models

Abstract: A new melatonin analogue 6-hydroxy-N-acetyl-β-oxotryptamine (1) was isolated from the marine-derived fungus Penicillium sp. KMM 4672. It is the second case of melatonin-related compounds isolation from microfilamentous fungi. The neuroprotective activities of this metabolite, as well as 3-methylorsellinic acid (2) and 8-methoxy-3,5-dimethylisochroman-6-ol (3) from Penicillium sp. KMM 4672, candidusin A (4) and 4″-dehydroxycandidusin A (5) from Aspergillus sp. KMM 4676, and diketopiperazine mactanamide (6) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 53 publications
2
32
0
1
Order By: Relevance
“…It was recently shown that fungal metabolites may exhibit neuroprotective activities in one or both 6-OHDA-and paraquat-induced Parkinson's disease models [40]. In the present work, 4-6 showed different activity profiles in the three neurotoxin-induced cell models.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…It was recently shown that fungal metabolites may exhibit neuroprotective activities in one or both 6-OHDA-and paraquat-induced Parkinson's disease models [40]. In the present work, 4-6 showed different activity profiles in the three neurotoxin-induced cell models.…”
Section: Discussionsupporting
confidence: 44%
“…Neuroblastoma Neuro-2a line cells (1 × 10 4 cells/well) were treated with the test compounds at concentrations of 10 µM for 1 h, and then the neurotoxins at different concentrations were added to the neuroblastoma cell suspensions [40]. Rotenone (Sigma-Aldrich, USA) was used at 10 µM.…”
Section: Neurotoxin-induced Cell Models Of Parkinson's Diseasementioning
confidence: 99%
“…KMM 4672. These compounds could produce neuroprotective activity against 6-OHDA- and PQ-induced neuronal toxicity [27,28]. Similarly, candidusin A ( 11 ) and 4-dehydroxycandidusin A ( 12 ) from Aspergillus sp.…”
Section: Potential Candidates From Marine-derived Compounds For Thmentioning
confidence: 99%
“…Fungi of the genus Aspergillus , section Circumdati ( Aspergillus insulicola , Aspergillus flocculosus , Aspergillus ochraceus , Aspergillus ochraceopetaliformis, and others) [2], are known to produce metabolites belonging to various chemical classes: aspyrone-related pentaketides [3,4], meroterpenoids [5,6], diketopiperazine alkaloids [7], drimane sesquiterpenoids and their nitrobenzoyl derivatives [8,9], steroids, and cerebrosides [10]. Many of them possess antimicrobial [4,10], antiviral [11], cytotoxic [8,11], and neuroprotective [12] activities.…”
Section: Introductionmentioning
confidence: 99%